APOE epsilon4 is associated with obstructive sleep apnea/hypopnea: the Sleep Heart Health Study. - Gottlieb, D J; DeStefano, A L; Foley, D J; Mignot, E; Redline, S; Givelber, R J; Young, T (Neurology, 2004)
BACKGROUND: Obstructive sleep apnea/hypopnea (OSAH) has a strong heritable component, although its genetic basis remains largely unknown. One epidemiologic study found a significant association between the APOE epsilon4 allele and OSAH in middle-aged adults, a finding that was not replicated in a cohort of elderly adults. The objective of this study was to further examine the association of the APOE epsilon4 allele with OSAH in a community-dwelling cohort, exploring age dependency of the association. METHODS: A genetic association study was performed, nested within a prospective cohort study of the cardiovascular consequences of OSAH. Unattended, in-home nocturnal polysomnography was used to measure apnea-hypopnea index (AHI) in 1,775 participants age 40 to 100 years. OSAH was defined as an AHI > or = 15. The relation of APOE genotype to prevalent OSAH was analyzed using generalized estimating equations to account for non-independent observations of individuals from the same sibship. RESULTS: At least one APOE epsilon4 allele was present in 25% of subjects, with 1.3% epsilon4/epsilon4 homozygotes. The prevalence of OSAH was 19%. After adjustment for age, sex, and BMI, the presence of any APOE epsilon4 allele was associated with increased odds of OSAH (OR 1.41, 95% CI 1.06 to 1.87, p = 0.02). The effect was approximately twice as great in subjects <75 (OR 1.61, CI 1.02 to 2.54) as in those > or =75 years old (OR 1.32, CI 0.91 to 1.90). Exploratory analyses revealed that the strongest effect of APOE epsilon4 was in subjects age <65 (OR 3.08, CI 1.43 to 6.64), and was stronger in those with hypertension or cardiovascular disease than in those without. CONCLUSION: The APOE epsilon4 allele is associated with increased risk of OSAH, particularly in individuals under age 65. The mechanisms underlying this association are uncertain. Age-dependency of the APOE-OSAH association may explain previous conflicting results.
Keywords: Adult; Age Distribution; Aged; Aged, 80 and over; Alleles; Apolipoprotein E4; Apolipoproteins E; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Genetic Predisposition to Disease; Genotype; Humans; Hyperlipidemias; Hypertension; Male; Middle Aged; Obesity; Polysomnography; Sleep Apnea, Obstructive; Smoking